Analisis Sistem Informasi Akuntansi Penjualan Dalam Upaya Meningkatkan Sistem Pengendalian Internal Pada PT X Di Surabaya - Rayfandy Rayfandy; Diana Zuhroh; Wiratna Wiratna; Chandra Chandra; Heri Toni (Jurnal Mahasiswa Manajemen dan Akuntansi, 2023)
This study aims to analyze how the sales accounting information system in an effort to improve the internal control system at PT. X. This type of research is a case study. Data collection techniques used are interviews, documentation, and observation. The data analysis technique used is descriptive technique, the steps taken to achieve the objectives of this study are (1) identification of sales accounting information systems. (2) analysis of the network of procedures that make up the sales accounting information system. (3) evaluation of weaknesses and potential risks in the application of sales accounting information systems. (4) analysis of recommendations on the application of sales accounting information systems for weaknesses and potential risks PT X control system has been running well, the company has a high commitment to satisfying all customer needs through the Implementation of the ISO 9001-2015 Quality Management System. The results showed that the weakness of the credit sales system of PT. X is in the credit function section, lack of searching for information about customer credit status, concurrent work. In addition, the company also does not apply payment terms, there is no agreement between the seller and the buyer with a cash discount, the term of payment, and the amount of the discount given.